2021
DOI: 10.1142/s2424835521500260
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Trapeziometacarpal Joint Osteoarthritis: A Meta-Analysis on Efficacy and Safety

Abstract: Background: Osteoarthritis of the thumb base is the second most prevalent arthritis of the hand. Management is primarily conservative, consisting of analgesia, splinting, physiotherapy, and steroid injections. Surgery is considered when conservative measures fail. Methods: The primary objective was to assess the safety and efficacy of the surgical interventions and therein, evaluate whether any superiority exists among the available interventions. Efficacy was evaluated by examining four parameters: pain, fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…24 Generally, functional outcomes following arthrodesis are considered to be comparable to other surgical techniques. 18,19 The current study found that arthrodesis has been associated with good clinical outcomes. Following surgical intervention, DASH score decreased by a mean of 32.6 points to 25.4 points postoperatively, and VAS score by 4.9 points to 1.9 points postoperatively, while grip strength increased by 7.3 kg to 23.0 kg postoperatively (46.5% increase).…”
Section: Discussionmentioning
confidence: 55%
“…24 Generally, functional outcomes following arthrodesis are considered to be comparable to other surgical techniques. 18,19 The current study found that arthrodesis has been associated with good clinical outcomes. Following surgical intervention, DASH score decreased by a mean of 32.6 points to 25.4 points postoperatively, and VAS score by 4.9 points to 1.9 points postoperatively, while grip strength increased by 7.3 kg to 23.0 kg postoperatively (46.5% increase).…”
Section: Discussionmentioning
confidence: 55%
“…Previous studies have reported that simple trapeziectomy, another common procedure for thumb CMC osteoarthritis, shows as good results overall as arthrodesis and T þ LRTI. 3,4 Moreover, they have shown that complication rate of simple trapeziectomy is lower than those of arthrodesis and T þ LRTI. 3,30 Therefore, a prospective study investigating long-term outcomes and complications (e.g., metacarpal subsidence, hyperextension of the MP joint, and osteoarthritis of adjacent joints) for a large number of patients is warranted to reveal an optimal procedure for middle-aged female workers with thumb CMC osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
“…1 There are several surgical procedures for thumb CMC osteoarthritis, including arthrodesis, trapeziectomy alone, trapeziectomy with ligament recon-struction and tendon interposition (T þ LRTI) arthroplasty, extension osteotomy, and artificial joint replacement; however, it has been demonstrated that there is no procedure that provides superior outcomes over another for thumb CMC osteoarthritis. [2][3][4] Traditionally, thumb CMC arthrodesis has been recommended for younger (aged < 50 years) high-demand patients, especially active males or manual workers, [5][6][7][8] whereas T þ LRTI has been utilized for low-demand patients or older patients. 5 We often encounter difficulty in deciding which surgical procedure to perform for female workers aged over 40 years since they are located at the border of the general consensus mentioned earlier.…”
Section: Introductionmentioning
confidence: 99%
“…71 All surgical techniques have demonstrated efficacy in pain relief and functional improvement. [72][73][74] A 2015 Cochrane review by Wajon et al 73 reported that of 7 surgical techniques, none was associated with better outcomes than alternative techniques for outcomes of functioning and pain.…”
Section: Treatment and Outcomesmentioning
confidence: 99%
“…In the US, the most commonly performed technique is trapeziectomy with ligament reconstruction and tendon interposition (>90%), followed by trapeziectomy alone, joint replacement, and fusion, all performed at a similar frequency . All surgical techniques have demonstrated efficacy in pain relief and functional improvement . A 2015 Cochrane review by Wajon et al reported that of 7 surgical techniques, none was associated with better outcomes than alternative techniques for outcomes of functioning and pain.…”
Section: Thumb Cmc Joint Arthritismentioning
confidence: 99%